PERBUATAN MELAWAN HUKUM DALAM TRANSAKSI JUAL BELI MELALUI INTERNET (E-COMMERCE) DIHUBUNGKAN DENGAN KETENTUAN BUKU III KUH PERDATA - , Anka Abdillah Nur, Sularto, S.H., C.N., M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The first study objective was to find the data used to compile a thesis to complete one of the conditions obtained his Master of Law Master of Law at the University of Gadjah Mada, the second is to determine the ratio of construction against the law in Law No.11 Year 2008 on Information and Transactions compared with the electronic book III Civil Code, and the third is to find out how sanctions against those who committed acts against the law in the sale and purchase transactions through the internet (e-commerce) as well as knowing the government's role in facilitating information and electronic transactions. The data used in this study were primary and secondary data collected through field research and library research. Means of collecting data is a study of the document. Subject of research by the authors is the parties who make a purchase agreement through internet media. Unlawful acts (Onrechtmatigedaad) as defined in Article 1365 Civil Code which states that: "Any unlawful act, which brings harm to another person, require the person who published the loss was his fault, replace the losses." Sanctions against the party who did against the law in the sale and purchase transactions through the internet (e-commerce) is being applied for compensation in a lawsuit in haldengan intentionally and without right to disseminate false and misleading news that resulted in the loss of consumers in electronic transactions Article 28 paragraph 1 of Law No.11 year RI 2008 on information and Electronic Transactions can be made to replace the losses have been suffered, the cost-recovery fee for public order and moral norms that have been disrupted and repair costs for damage suffered as a direct result of Defendants unlawful conduct is in accordance with Article 45, paragraph 2 of Law ITE any person who meets the elements referred to in Article 28 paragraph 1 or paragraph 2 shall be punished with imprisonment of 6 (six) years and / or a fine of not more Rp.1.000.000.000, - (one billion rupiah ) .. The role of government to protect the public interest of any kind of disturbance as a result Any use of Electronic Information and Electronic Transaction that disrupt public order, in accordance with the provisions of legislation. This section does not correspond to reality because there are igniter use of electronic information that could disrupt public order that means the government has not protected the public interest.